AP2a enhanced the osteogenic differentiation of mesenchymal stem cells by inhibiting the formation of YAP/RUNX2 complex and BARX1 transcription. (15th November 2018) - Lin, Xiao; Yang, Haoqing; Wang, Lijun; Li, Wenzhi; Diao, Shu; Du, Juan; Wang, Songlin; Dong, Rui; Li, Jun; Fan, Zhipeng
Abstract: Objectives: Bone regeneration by bone tissue engineering is a therapeutic option for bone defects. Improving the osteogenic differentiation of mesenchymal stem cells (MSCs) is essential for successful bone regeneration. We previously showed that AP2a enhances the osteogenic differentiation in MSCs. The present study investigated the mechanism of how AP2a regulates the direct differentiation. Materials and methods: Co‐immunoprecipitation and ChIP assays were carried out to investigate the underlying mechanism in MSCs differentiation. The osteogenic differentiation potential was determined by mineralization ability and the expression of osteogenic marker in vitro and the in vivo bone‐like tissue generation in nude mice. Results: We show that AP2a can compete with RUNX2, a key transcription factor in osteogenic differentiation, to recruit YAP and release the inhibition of RUNX2 activity from YAP by forming YAP‐AP2a protein complex. YAP‐AP2a protein complex also interacts with the BARX1 promoter through AP2a, inhibit the transcription of BARX1. Moreover, BARX1 inhibits osteogenic differentiation of MSCs. Conclusions: Our discoveries revealed that AP2a may regulate the osteogenic differentiation in an indirect way through competing with RUNX2 to relieve the RUNX2 activity which inhibited by YAP, and also in a direct way via targeting the BARX1 and directly repressed its transcription. Thus, our discoveries shed new light on the mechanism of direct differentiation of MSCs and provide candidate targets for improving the osteogenic differentiation and enhancing bone tissue regeneration.